Measurements of WH and ZH production with Higgs boson decays into bottom quarks and direct constraints on the charm Yukawa coupling in 13 TeV pp collisions with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Sanfilippo, Lorenzo; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Journal of high energy physics, 2025)
A study of the Higgs boson decaying into bottom quarks (H → bb¯) and charm quarks (H → cc¯) is performed, in the associated production channel of the Higgs boson with a W or Z boson, using 140 fb−1 of proton-proton collision data at √s = 13 TeV collected by the ATLAS detector. The individual production of W H and ZH with H → bb¯ is established with observed (expected) significances of 5.3 (5.5) and 4.9 (5.6) standard deviations, respectively. Differential cross-section measurements of the gauge boson transverse momentum within the simplified template cross-section framework are performed in a total of 13 kinematical fiducial regions.